Supervisor support, self-efficacy, and employee performance: The mediating role of office de-clutter - Farida Saleem; Muhammad Imran Malik; Awais Qasim (Administrative Sciences, 2022)
The study aims to test the impact of social support from supervisors and self-efficacy on employee performance through office de-clutter (a mediator) in banks. During the COVID-19 pandemic, the supporting factors (social support and self-efficacy) to de-clutter for maintaining employee performance is a novel contribution to the literature and is supported by the social exchange theory-SET. The employee's performance can be maintained with lower levels of office clutter (de-clutter). The office clutter can be managed through the availability of managerial social support and employee self-efficacy. The impact of supervisor support and self-efficacy on employee performance is examined through the lens of the social exchange theory. A cross-sectional and quantitative study was conducted with 202 primary responses from bank employees. The responses were recorded using closed-ended questionnaires. A response rate of 73.9% was achieved. Reliability and validity were assessed using Cronbach's alpha scores and AVE, respectively. PLS-SEM was used as a data analysis and hypotheses testing technique. The results revealed that supervisors' social support and self-efficacy significantly and positively affect employee performance. Moreover, supervisors' social support and self-efficacy helped in office de-clutter, further ensuring better performance.
Keywords: 350; bank employees; COVID-19; office de-clutter; performance; self-efficacy; social exchange theory; supervisors' support